Biodegradable poly (l-lactic acid) (PLLA) and PLLA-3-arm blend membranes: The use of PLLA-3-arm as a plasticizer. (July 2017) - Neumann, Ivan Antonio; Flores-Sahagun, Thais Helena Sydenstricker; Ribeiro, Andreza Maria
Abstract: The use of biodegradable polymers in regenerative tissue engineering and bone implants is increasingly practiced in the biomedical area due to their good mechanical properties, good biocompatibility and complete degradation in living organisms, without adverse side effects. Poly (l -lactic acid) (PLLA) is a biodegradable polymer, largely used in bioengineering, although features such as high rigidity and hydrophobicity limit its use in some areas. The aim of this work was to investigate the synthesis of PLLA and PLLA-3-Arm (a copolymer of PLLA and glycerol) through bulk polymerization for the subsequent production of blends of both polymers at different ratios. This was followed by their characterization through differential scanning calorimetry, FTIR, thermogravimetric analysis, tensile tests and contact angle measurements. Increased hydrophilicity and higher values of plastic deformation were obtained for the materials when the PLLA-3-Arm ratio was increased, showing promising potential for use in bioengineering. The degradation of the samples was evaluated in phosphate buffer solution (PBS) for 28 and 56 days. Scanning electron microscopy (SEM) images of PLLA and blends showed different degradation behavior with distinct morphologies, which can be attributed to the presence of Glycerol/PLLA-3-Arm in the formulation. Graphical abstract: